The Arabidopsis APOLO and human UPAT sequence-unrelated long noncoding RNAs can modulate DNA and histone methylation machineries in plants - Fonouni-farde, Camille Audrey (2022)
Background: RNA-DNA hybrid (R-loop)-associated long noncoding RNAs (lncRNAs), including the Arabidopsis lncRNA AUXIN-REGULATED PROMOTER LOOP (APOLO), are emerging as important regulators of three-dimensional chromatin conformation and gene transcriptional activity. Results: Here, we show that in addition to the PRC1-component LIKE HETEROCHROMATIN PROTEIN 1 (LHP1), APOLO interacts with the methylcytosine-binding protein VARIANT IN METHYLATION 1 (VIM1), a conserved homolog of the mammalian DNA methylation regulator UBIQUITIN-LIKE CONTAINING PHD AND RING FINGER DOMAINS 1 (UHRF1). The APOLO-VIM1-LHP1 complex directly regulates the transcription of the auxin biosynthesis gene YUCCA2 by dynamically determining DNA methylation and H3K27me3 deposition over its promoter during the plant thermomorphogenic response. Strikingly, we demonstrate that the lncRNA UHRF1 Protein Associated Transcript (UPAT), a direct interactor of UHRF1 in humans, can be recognized by VIM1 and LHP1 in plant cells, despite the lack of sequence homology between UPAT and APOLO. In addition, we show that increased levels of APOLO or UPAT hamper VIM1 and LHP1 binding to YUCCA2 promoter and globally alter the Arabidopsis transcriptome in a similar manner. Conclusions: Collectively, our results uncover a new mechanism in which a plant lncRNA coordinates Polycomb action and DNA methylation through the interaction with VIM1, and indicates that evolutionary unrelated lncRNAs with potentially conserved structures may exert similar functions by interacting with homolog partners.